PARTICIPATION OF THE ARMED FORCES OF PERU IN THE NATIONAL HEALTH EMERGENCY DUE TO COVID-19 - Pizarro Carrillo, Victor (2021)
The role played by the Armed Forces has been changing, leading to an increasingly active and strategic parti-cipation, based on the intertwining of their functions with the security and internal order of a given country. This new conception has been reflected in the legal norms, by including the Armed Forces in the internal order, thus expanding their functions towards a social aspect. Based on the above, the objective of this research was to delimit the measures taken in the face of the health emergency by COVID-19 and how these made the active participation of the Armed Forces in the internal control of the country viable. The research was descriptive and qualitative in approach. The unit of analysis was made up of normative documents referring to security and defense, both at national and international level, and more specifically those normative documents related to policies of participation of the Armed Forces with respect to the national security and defense of Peru within the framework of COVID-19, as well as the actions that were executed based on these decrees. As for the data collection techniques, direct observation and documentary analysis were used and, with respect to the infor-mation collection instruments, bibliographic files were used, which were organized according to two variables of analysis: capacity of the Armed Forces and participation in the health emergency. It was found that the legisla-tive decrees granted constitutionality to the actions carried out by the Armed Forces to maintain internal order, therefore, it was concluded that the current Constitution enables the Armed Forces to participate in security in cases of internal order, based on the needs and emergencies that may arise.